A Study on Handling of Distributed Database Security Threats: Ensuring Security in Distributed Database Systems (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Distributed database is an assortment of databases that can be put away at various PC arranges and can be access from various areas. For a distributed environment, improvement of a made sure about database is a basic issue. These days, distributed database turned out to be increasingly well known and thus the significance of guaranteeing security of database in distributed environment turned out to be progressively noteworthy. Right now, highlights of the distributed database system and its security issues are referenced. Security issue may bargain the access control and the honesty of the system. Some answer for security angles like access control, unwavering quality, uprightness and secrecy are additionally referenced.